Analysis of the use of fortified medium in continuous culture of mammalian cells - Gambhir, Anshu (Kluwer Academic Publishers, 1999)
Continuous culture is frequently used in the cultivation of mammalian cells for the manufacturing of recombinant protein pharmaceuticals. In such operations a large volume of medium is turned over each day, especially in the case where cell recycle, or perfusion cultivation, is practiced. In principle, the volumetric throughput of medium can be reduced by using a more concentrated feed while maintaining the same nutrient provision rate. Overall, the medium components are divided into two categories: ‘consumable nutrients' and ‘unconsumable inorganic bulk salts’. In such fortified medium, the concentrations of consumable nutrients, but not bulk salts, are increased. With a stoichiometrically-balanced medium, the large amount of nutrients fed into the culture is largely consumed by cells to give rise to residual concentrations of these nutrients in their optimal range. However, unless care is taken to initiate the continuous culture, overshoot of nutrients may occur during the transient period. The high nutrient concentration during overshoot may be inhibitory by itself, or the resulting high osmolality may retard the growth. Using a mathematical model that incorporates the growth inhibitory effect of high osmolality we demonstrate such a potentially catastrophic effect of nutrient and osmolality overshoot by simulation. To avoid overshoot a controlled nutrient feeding scheme should be devised at the initiation of continuous culture.